PENGARUH PARTISIPASI PENGANGGARAN TERHADAP BUDGETARY SLACK DENGAN ETIKA, BUDAYA ORGANISASI, OPPORTUNISTIC BEHAVIOUR DAN KETIDAKPASTIAN LINGKUNGAN SEBAGAI PEMODERASI - Asih, Ni Putu Yuni; Astika, Ida Bagus Putra; Dwija Putri, I.G.A Asri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
The purpose of this study was to obtain empirical evidence on the effect of budgetary participation on budgetary slack with ethics, organizational culture, opportunistic behaviour and environmental uncertainty as moderating. Methods of data collection in this study used a questionnaire with a sample size of this study was 106 Echelon II, III, IV SKPD Jembrana were selected based on purposive sampling method. Data analysis technique used is the technique moderation regression analysis (MRA). Ethics Variable does not moderate the effect of budgetary participation on budgetary slack, Organizational culture variable does not moderate the effect of budgetary participation on budgetary slack, opportunistic behaviour variable does not moderate the effect of budgetary participation on budgetary slack. environmental uncertainty variable positive and strengthening effect of budgetary participation on budgetary slack. Based on the research results suggested that SKPD build integrated systems in local budgeting in order to create the effectiveness of the organization's budget.
Keywords: participation budgeting, ethics, organizational culture, opportunistic behaviour, environmental uncertainty. budgetary slack